KETERLIBATAN PEREMPUAN TANI PEMILIK TANAH PADA PROGRAM REDISTRIBUSI TANAH DALAM RANGKA MENCAPAI KESEJAHTERAAN EKONOMI RUMAH TANGGA (Studi Kasus di Desa Candirejo, Kecamatan Ponggok, Kabupaten Blitar) - Eko Wahyu Budiman; Brillian Pintakami, Lintar (Universitas Islam Balitar, 2019)
This study aims to describe the extent of involvement of women landowners in managing their land and analyze the dual role of women landowners and the contribution of women landowner income to household economic welfare from the Land Redistribution program in Blitar District. The research method uses a qualitative approach. Data was collected through Focus Group Discussion (FGD), In-depth Interviews, participatory observation, and documentation.Determination of the sample using the snowball sampling technique and obtained 30 informants as farmers (male and female). The selection of 8 key informants was determined by purposive sampling. Data analysis uses Harvard Model gender analysis techniques, qualitative analysis of phenomenology, and analysis of household income contribution. The results showed that in 12 stages of productive activities 6 activities were carried out by farmers again, 2 activities were carried out by women farmers, and 4 activities were carried out together. The division of gender activities shows that 71% of reptoductive activities are carried out by women landowners or wives. Whereas the social activities of women devote the same time with a percentage of 50%. However, in the formal management of the Land Redistribution program and coaching there is no special attention to the role of women in the management and sustainability of the program. The contribution of women landholders to household income is Rp. 31,900,530 / year or 50% of total household income. Nevertheless, women who own land are able to allocate their time to continue to carry out their reproductive roles in the household while men do not. This research proves that women landowners have the potential to achieve successful management of agricultural land and are able to improve household economic prosperity.